Principles and Methods of Analysis of Communicative – Pragmatic Features of Complete Sentences - Sobirova Dilafruz Akrom qizi (International Journal on Integrated Education, 2022)
During the beyond few years the concept of the real department of the sentence has been criticized for its binary man or woman. The critics of the concept say that it isn't always continually feasible to divide a sentence into components and that it's far sufficient to set up simplest the point of interest or the middle of records However, linguists hold to discover the records shape of the sentence and propose that rather than the 2 classes of topic and rheme, there must be 3, 5 or even six units.